Type 2 diabetes in adolescents and young adults. Issue 1 (January 2018) - Lascar, Nadia; Brown, James; Pattison, Helen; Barnett, Anthony H; Bailey, Clifford J; Bellary, Srikanth
Summary: The prevalence of type 2 diabetes in adolescents and young adults is dramatically increasing. Similar to older-onset type 2 diabetes, the major predisposing risk factors are obesity, family history, and sedentary lifestyle. Onset of diabetes at a younger age (defined here as up to age 40 years) is associated with longer disease exposure and increased risk for chronic complications. Young-onset type 2 diabetes also affects more individuals of working age, accentuating the adverse societal effects of the disease. Furthermore, evidence is accumulating that young-onset type 2 diabetes has a more aggressive disease phenotype, leading to premature development of complications, with adverse effects on quality of life and unfavourable effects on long-term outcomes, raising the possibility of a future public health catastrophe. In this Review, we describe the epidemiology and existing knowledge regarding pathophysiology, risk factors, complications, and management of type 2 diabetes in adolescents and young adults.